A Byzantine consensus based on proof-of-work of nodes' behaviors. (November 2020) - Dingyu, Wang; Dingmin, Wang; Lupin, Qin; MinLong, Xu
Abstract: Blockchain is a decentralized distributed peer-to-peer system, and decision-making in the system relies on a reliable consensus protocol. Under the current consensus protocol in the blockchain system, the behavior of nodes are not regulated. Based on the existing consensus protocol, this paper analyzes the problems encountered in application scenarios, introduces a credit calculation method to regulate the behavior of system nodes, and with a simplified consistency protocol, it can promote the alliance chain system to enter a virtuous cycle, and improve the efficiency of consensus in scenarios with many wrong nodes.